Do radiolucencies affect the outcomes of a 4th generation total ankle prosthesis? A 2-year follow-up. Issue 1 (February 2023) - Gross, Christopher; Friscia, David A.; Doty, Jesse F.; Murphy, G. Andrew; Bohay, Donald; Fortin, Paul; Vora, Anand; Strasser, Nicholas L.
Category: Ankle Arthritis; Ankle Introduction/ Purpose: Fourth generation ankle replacements benefit from improved surgical technique, respect for bony preservation, and increased surgeon awareness of operative indications. The rate of radiolucencies around the tibial component observed in studies about 3rd generation total ankle replacements are reported at rates that range from 30% to 43%. To date, studies have not been shown to predict survivorship or patient reported outcomes (PROs) however. We hypothesize that radiolucenices do not affect PROs or survivorship. Methods: Patients presenting for a total ankle replacement at 9 institutions were prospectively enrolled in academic and private settings. Each patient received an INFINTY ankle prosthesis (Stryker, Memphis, TN, USA). Implants were assessed for subsidence and the presence of radiolucencies based on the analysis and comparison of all postoperative weightbearing ankle radiographs available. Subsidence was defined as a change of tibial component alignment greater than 5degrees or a change in the vertical position of the talar component of 5 mm or more. Subsidence and radiolucent lines were deemed nonprogressive when no change in position or size was noted with comparison of the last 2 radiographs. PROMs were recorded pre-operatively and at 6months, 12months, and 24month intervals. The following PROMs were collected: Ankle Osteoarthritis Score (AOS), PROMIS Global Physical Health, and Foot and Ankle Outcome Score (FAOS). The preoperative and latest follow-up scores for patients with two years of follow-up were analyzed. Results: 110 patients were enrolled in the study who had 2-year follow-up with twenty-one patients (19.1%) exhibiting a radiographic lucency. To date, our survivorship is 97.3%, of which 2 patients were revised for aseptic loosening; both reporting radiolucencies. The radiolucencies for one identified at 6months became progressive for both tibia and talus with cysts above 5mm requiring revision at 1.5years post op. The other requiring revision at 2years post-op reported progressive radiolucency. There was no difference in rates of survivorship with or without radiolucencies. One patient had subsidence which required revision. All patients with radiolucencies had significant improvements in all domains of the AOS, PROMIS, and FAOS Scores (p< 0001). Radiolucency did not impact the PROs (AOA p=.741, PROMIS p=.964, FAOS p=.8937) in those with 2-year follow-up. Conclusion: Radiolucencies did not impact PROMs in patients undergoing implantation with a 4th generation total ankle replacement. In carefully selected patients, radiolucency did not correlate with an increased need for revision surgery nor had decreased survivorship.